Fe/ZSM-11 as a novel and efficient photocatalyst to degrade Dichlorvos on water solutions - Gomez, Silvina (2017)
Iron modified ZSM-11 zeolites were tested as heterogeneous catalysts in the photodegradation of Dichlorvos water solutions. ZSM-11 zeolite matrixes were synthesized by the hydrothermal method and iron was incorporated by the wet impregnation method in four different concentrations. Catalysts samples were characterized by several techniques (XRD, BET, UV–vis DRS, ICP-OES, TPR, EPR) in order to confirm structure, crystallinity and iron species present. α-Fe2O3 was detected by XRD in higher iron content samples and it presence was confirmed by EPR, TPR and UV–vis DRS. Band gap energies for Fe/ZSM-11 samples were closer to that reported for pure α-Fe2O3. The materials so far characterized were tested as heterogeneous catalyst in Dichlorvos photodegradation. Fe/ZSM-11 with a 6 wt% of iron incorporation showed the best catalytic behavior. Higher iron loadings showed lower degradation efficiencies. This material is reusable for at least six catalytic cycles without considerable differences among the DDVP amount degraded.